Narratives of resistance to technological change: Drawing lessons for urban energy transitions in southern Chile. (July 2020) - Boso, Àlex; Garrido, Jaime; Álvarez, Boris; Oltra, Christian; Hofflinger, Álvaro; Gálvez, Germán
Highlights: Air pollution is a major environmental risk in urban southern Chile. Semi-structured interviews and news analysis were combined to explore narratives. Early disruptions in energy transitions produce narratives of resistance to change. The clash between hero and horror stories slows down urban energy transitions. Framing technology over-optimistically can erode the diffusion of new energy systems. Abstract: Several cities in southern Chile are immersed in energy transition processes due to the severe air pollution that the massive use of firewood for domestic heating and cooking has generated. Semi-structured interviews and news analysis of local newspapers were combined to explore the narratives of residents of Temuco and Padre Las Casas, two of the most polluted cities in Latin America. The study uses some aspects of the innovation systems theory to try to understand the social origins of the narratives of resistance to technological change in a city where most homes use wood-burning stoves and cookers. Few studies have employed narratives to study urban energy transitions. A rich narrative about the complexity of technological change emerged from the interviews, offering valuable insights into energy transition research. The results show the relevance of early events in energy transitions in the development of these transitions. The narrative dichotomy between hero and horror stories emerges as a social mechanism capable of slowing the diffusion of emerging energy technologies. The findings of this study suggest that narratives of resistance to change constitute a critical issue that local governments must learn to manage in the transitions toward scenarios of greater urban sustainability.